Tailoring postoperative management through sentinel lymph node biopsy in low- and intermediate-risk endometrial cancer - the SENTRY clinical trial - Sorokin, P; Novozhilov, M; Utkin, D; Abduragimova, Z; Dudina, I; Nikiforchin, A; Kulikova, S (Klinicka onkologie, 2024)
BACKGROUND: While total hysterectomy and bilateral salpingo-oophorectomy without lymph node staging are standard for low- and intermediate-risk endometrial cancer, certain histopathologic factors revealed after surgery can necessitate additional interventions. Our study assessed the influence of sentinel lymph node biopsy on postoperative decision-making. MATERIALS AND METHODS: In the SENTRY trial (July 2021 - February 2023), we enrolled patients with International Federation of Gynaecology and Obstetrics (FIGO) stage IA-IB low-grade endometrioid endometrial cancer. Laparoscopic sentinel lymph node mapping using indocyanine green was performed alongside total hysterectomy with bilateral salpingo-oophorectomy. Subsequent management changes based on sentinel lymph node biopsy results were evaluated. The trial was registered at ClinicalTrials.gov (NCT04972682). RESULTS: Of the 100 enrolled participants, a bilateral detection rate of 91% was observed with a median detection time of 10 min (interquartile range 8-13 min). Sentinel lymph node metastases were found in 8% (N = 8) of participants. Postoperative FIGO staging increased in 15% (N = 15) and decreased in 5% (N = 5) of patients. Sentinel lymph node biopsy results altered the adjuvant treatment plan for 20% (N = 20): external beam radiotherapy was omitted in 12% (N = 12) while 6% (N = 6) had external beam radiotherapy +/- systemic chemotherapy added due to sentinel lymph node metastases. In 2% (N = 2), the external beam radiotherapy field was expanded with the paraaortic region. No intraoperative complications were reported and no 30-day major morbidity and mortality occurred. Throughout a median follow-up of 14 (95% CI 12-15 months, neither patient-reported lymphedema nor pelvic recurrence surfaced in the cohort. CONCLUSIONS: Sentinel lymph node biopsy using indocyanine green is a safe procedure and allows tailoring adjuvant therapy in presumed low- and intermediate-risk endometrial cancer. It assists in avoiding external beam radiotherapy overtreatment and introducing additional modalities when necessary.
Keywords: senioři; Uterine cancer; pooperační péče; Indocyanine Green; gynecological cancer; Carcinoma, Endometrioid; Sentinel Lymph Node Biopsy; indokyanová zeleň; Middle Aged; lymfatické metastázy; adjuvant treatment; Laparoscopy; Hysterectomy; nádory endometria; Endometrial Neoplasms; Salpingo-oophorectomy; Lymphatic Metastasis; Neoplasm Staging; salpingo-ooforektomie; ženské pohlaví; endometroidní karcinom; Humans; radiotherapy; lidé středního věku; indocyanine green; Drug therapy; staging nádorů; hysterektomie; biopsie sentinelové lymfatické uzliny; Female; laparoskopie; Aged; sentinel lymph node; Postoperative Care; lidé